Hubungan antara Umur dengan Bobot Non Karkas Internal dan Eksternal pada Babi Duroc Jantan di RPH Mabar Medan - S.N. Aritonang; J. Pinem; T. A. Pelawi (Universitas Andalas, 2011)
The purposed of this research was analyzed the relationship of pigs age with internal and external non carcass weight of male Duroc pigs. The experiment has been carried out on one hundred and twenty male Duroc pig, which consisted of four aged groups : A (240-270 days), B (271-300 days), C (301-330 days) and D (331-360 days). The method of this research was survey method by purposive quota sampling in Mabar Slaugther House, Medan. The variables were observed of internal and external non carcass weigth (head and foot) of male Duroc pigs. The relation of animal age and variable measured is used the quadratic regression analysis. The result indicated that there are closely relation (P<0,01) between animal age with internal and external non carcass weigth (head and foot) of male Duroc pig with correlation coefficient of 0.953; 0.992 and 0.950.